Toksisitas Akut dan Penentuan DL50 Oral Ekstrak Air Daun Gandarusa (Justicia gendarussa Burm. F.) pada Mencit Swiss Webster - Andreanus A. Soemardji; Endang Kumolosasi; Cucu Aisyah (Jurnal Matematika & Sains, 2002)
Acute toxicity test of water extract of âgandarusaâ (Justicia gendarussa Burm F.) leaves in Swiss Webster mice and oral median lethal dose (LD50) determination by four methods had been performed. Results showed that âgandarusaâ leaves have toxic effect on central nerveus system. Oral LD50 by Miller-Tainter method, Reed-Muench method, KÃ¤rber method, and calculation method of Farmakope Indonesia 3rd edition in male mice had the same value as that in female mice i.e. 21.00, 21.03, 22.50, and 21.60 g/kg body weight respectively. Miller-Tainter method produced the lowest LD50 value.